Unprecedented nesting activity by the Golden Eagle Aquila chrysaetos in the Foreste Casentinesi, Monte Falterona and Campigna National Park (Avocetta, 2017)
The Golden Eagle Aquila chrysaetos is present with one pair in the Foreste Casentinesi National Park, where it has been regularly monitored since 1993. Between 1993 and 1999 it nested on a rock at 900 m a.s.l.; then it built at least 4 nests on large fir trees along the north slopes with dense forest cover. Tab. 1 summarizes nesting data. The nest located on the rock was used 10 times with the fledging of 8 young; confirmed nesting on fir trees was observed on 7 occasions, while in 3 other occasions breeding could not be confirmed; 5 young fledged from the nests on fir trees. Two fledglings occurred in 1993 (rock) and again after 24 years in 2016 (fir). In 2016 a research program was carried out in the Sasso Frati Nature Reserve, within the National Park of Foreste Casentinesi, M. Falterona and Campigna, in the Romagna region (province of Forlì Cesena, Italy). A 10x binoculars and 20-60x telescopes were utilized for direct observations. The reproduction phase was followed regularly between March and August. The 2016 breeding (after 6 years of apparent failures) is unprecedented for the great difference in the development between the two chicks, the first fledged in mid-July (between 12 and 18) while the second left the nest in mid August (between 13 and 21), with a delay of about one month compared to its sibling.